The features of the functioning of speech contact tools in artistic text and the issue of their translation (based on German prose) - Fokeeva, Yuliya Aleksandrovna; Dubovitskaya, Mariya Andreevna; Shapovalova, Ol'ga Nikolaevna (Филология: научные исследования, 2025)
The subject of the study is the specificity of the use of means of speech contact (MSC) in artistic literature, primarily in the direct speech of characters. The object of the study is the problem of their translation from German to Russian. The aim of the research is to identify the most important patterns that emerge in the transmission of means of speech contact in artistic translation from German to Russian. Special attention is paid to the fact that means of speech contact are an integral component of communication, which is reflected in the speech of characters in works of art from different eras. The authors consider aspects of the topic such as the translator's ability to take into account the historical atmosphere, the character and emotional state of the heroes, their social affiliation, and other characteristics. The theoretical basis of the research comprises works in the field of communication theory and translation theory. In addressing the research tasks, the following methods were employed: linguistic description to identify the features of the functioning of various groups of means of speech contact in the artistic text, comparative analysis to highlight the ways of conveying MSC through the means of the target language, and contextual analysis to account for the influence of context on the translation decision, including the type of communication among characters and other components. The scientific novelty of the research lies in the fact that it systematically categorizes means of speech contact based on works set in the 19th century, as well as contemporary German prose, and additionally examines these means from the perspective of translation. As a result, it has been established that the most significant groups of the studied units consist of addresses, etiquette formulas, and introductory-contact components, with a noticeable increase in the importance of imperative constructions in contemporary prose. In the translation of means of speech contact used in formal communication situations, lexical equivalents are more actively employed, whereas for conveying informal addresses and imperative constructions, a tendency towards selecting variant equivalents is observed, requiring consideration of factors such as the described era, the relationships between the characters of the work, their emotional state, and the existence of equivalent matches in the target language. The practical significance of the research consists in the possibility of using its materials and conclusions in the courses "Translation Theory" and "Artistic Translation" for students of philological specialties.